Proresolving mediators LXB4 and RvE1 regulate inflammation in stromal cells from patients with shoulder tendon tears - Dakin, S; Colas, R; Wheway, K; Watkins, B; Appleton, L; Rees, J; Gwilym, S; Little, C; Dalli, J; Carr, A (Elsevier, 2019)
Tendon stromal cells isolated from patients with chronic shoulder rotator-cuff tendon tears show dysregulated resolution responses. Current therapies do not address the biological processes concerned with persistent tendon inflammation, therefore new therapeutic approaches targeting tendon stromal cells are required. We determined if two specialised pro-resolving mediators (SPM) LXB4 and RvE1, modulated the bioactive lipid mediator profiles of IL-1β stimulated tendon cells derived from patients with shoulder tendon tears and healthy volunteers. We also determined if LXB4 or RvE1 treatments moderated the pro-inflammatory phenotype of tendon tear stromal cells. Incubation of IL-1β treated patient-derived tendon cells in LXB4 or RvE1 upregulated concentrations of SPM. RvE1 treatment of diseased tendon stromal cells increased 15-epi-LXB4 and regulated PGF2α. LXB4 or RvE1 also induced expression of the SPM biosynthetic enzymes 12-liopxygeanse (ALOX12), and ALOX15. RvE1 treatment upregulated proresolving receptor ERV1 compared to vehicle treated cells. Incubation in LXB4 or RvE1 moderated the proinflammatory phenotype of patient derived tendon tear cells, regulating markers of tendon inflammation, including Podoplanin, CD90, pSTAT-1 and IL-6. LXB4 and RvE1 counter-regulate inflammatory processes in tendon stromal cells, supporting the role of these molecules as potential therapeutics to resolve tendon inflammation.